Keeping those gender gains - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Institutionalizing Gender Equality. Commitment, policy and practice, a global source book A co-publication of the KIT Press, Royal Tropical Institute, Amsterdam and Oxfam Publications, Oxford. 2001. 174 pp. ISBN 0 85598 459 7 (Oxfam edition) GBP 12.95